Analysis of the maturity of the development process of products associated with industry 4.0 in the capixaba market through applied research - Carvalho, Flávio Lucio Santos de; Ferreira, Juliana Loureiro (Brazilian Journal of Production Engineering, 2022)
This article aimed to measure the maturity of the product development process (PDP) in the industrial sector of the state of Espírito Santo, relating it to industry 4.0, that is, to verify the knowledge and application of companies in Espírito Santo regarding the product development process, the application of industry 4.0 concepts and how they use such processes as a competitive advantage to leverage results, standing out in the Espírito Santo Industry, companies that have production efficiency as pillars and with a PDP approach to establish themselves in the market. Therefore, the way in which companies find ways to achieve this goal is the focus on the product development process, which “if well managed can decisively contribute to the competitiveness of companies in this environment” (JUGEND, 2006). To sequence the project, three pillars of the PDP were considered: production efficiency, lead time and assembly line flexibility. For this, a screening was carried out in companies headquartered in Espírito Santo and only those with a product development process were evaluated. In this sense, the aim was to analyze the positioning of these companies, demonstrate solutions and improvements for product development and the need for a program to improve the product process. The result obtained was the verification of the immaturity of the market regarding PDP and that the role of production engineers in the development of Espirito Santo products is small compared to other professionals working in the PDP segment and companies do not use all the quality tools for the PDP.